RVSVΔG-ZEBOV-GP (also designated V920) recombinant vesicular stomatitis virus pseudotyped with Ebola Zaire Glycoprotein: Standardized template with key considerations for a risk/benefit assessment. (11th April 2019) - Monath, Thomas P.; Fast, Patricia E.; Modjarrad, Kayvon; Clarke, David K.; Martin, Brian K.; Fusco, Joan; Nichols, Richard; Heppner, D. Gray; Simon, Jakub K.; Dubey, Sheri; Troth, Sean P.; Wolf, Jayanthi; et al.
Abstract: The Brighton Collaboration Viral Vector Vaccines Safety Working Group (V3SWG) was formed to evaluate the safety and characteristics of live, recombinant viral vector vaccines. A recent publication by the V3SWG described live, attenuated, recombinant vesicular stomatitis virus (rVSV) as a chimeric virus vaccine for HIV-1 (Clarke et al., 2016). The rVSV vector system is being explored as a platform for development of multiple vaccines. This paper reviews the molecular and biological features of the rVSV vector system, followed by a template with details on the safety and characteristics of a rVSV vaccine against Zaire ebolavirus (ZEBOV). The rVSV-ZEBOV vaccine is a live, replication competent vector in which the VSV glycoprotein (G) gene is replaced with the glycoprotein (GP) gene of ZEBOV. Multiple copies of GP are expressed and assembled into the viral envelope responsible for inducing protective immunity. The vaccine (designated V920) was originally constructed by the National Microbiology Laboratory, Public Health Agency of Canada, further developed by NewLink Genetics Corp. and Merck & Co., and is now in final stages of registration by Merck. The vaccine is attenuated by deletion of the principal virulence factor of VSV (the G protein), which also removes the primary target for anti-vector immunity. The V920 vaccine caused no toxicities after intramuscular (IM) or intracranial injection of nonhuman primates and no reproductive or developmental toxicity in a rat model. In multiple studies, cynomolgus macaques immunized IM with a wide range of virus doses rapidly developed ZEBOV-specific antibodies measured in IgG ELISA and neutralization assays and were fully protected against lethal challenge with ZEBOV virus. Over 20, 000 people have received the vaccine in clinical trials; the vaccine has proven to be safe and well tolerated. During the first few days after vaccination, many vaccinees experience a mild acute-phase reaction with fever, headache, myalgia, and arthralgia of short duration; this period is associated with a low-level viremia, activation of anti-viral genes, and increased levels of chemokines and cytokines. Oligoarthritis and rash appearing in the second week occur at a low incidence, and are typically mild-moderate in severity and self-limited. V920 vaccine was used in a Phase III efficacy trial during the West African Ebola epidemic in 2015, showing 100% protection against Ebola Virus Disease, and it has subsequently been deployed for emergency control of Ebola outbreaks in central Africa. The template provided here provides a comprehensive picture of the first rVSV vector to reach the final stage of development and to provide a solution to control of an alarming human disease.